Purification and selected biochemical properties of peroxidase from cress (Lepidium sativum sub sp. sativum). Issue 1 (1st January 2018) - Altay, Ahmet; Koktepe, Tubanur; Durmaz, Lokman; Topal, Fevzi; Gülçin, İlhami; Köksal, Ekrem
ABSTRACT: Cress ( Lepidium sativum ) is an annual herb from Brassicaceae family, and in some regions. It is known as peppergrass, garden cress, garden peppercress, pepperwort, or poor man's pepper. Cress is an important medicinal plant in some countries including Turkey. This plant has major scientific and therapeutic significance. Peroxidase (POD, E.C.1.11.1.7) is an oxidoreductase enzyme produced by a number of organisms. In this study, POD enzyme was purified from cress by ammonium sulphate precipitation, gel filtration, and CM-Sephadex ion-exchange chromatographies. Km and Vmax values were calculated from the Lineweaver-Burk graph for H2 O2 and guaiacol substrates and the substrate specificity of POD was investigated. The results showed that substrate specificity of H2 O2 is better than substrate specificity of guaiacol for this enzyme. The inhibition effects of three cations (Al 3+, Cu 2+,  and Cr 3+ ) and one organic compound of cetyl trimethylammonium bromide were performed and their inhibition types were determined. Finally, optimum pH, optimum temperature, optimum ionic strength, and stable pH were determined.